Hospitalizations for Cardiovascular Disease After Liver Transplantation in the United States1. Issue 10 (25th October 2018) - Khurmi, Narjeet S.; Chang, Yu‐Hui; Eric Steidley, D.; Singer, Andrew L.; Hewitt, Winston R.; Reddy, Kunam S.; Moss, Adyr A.; Mathur, Amit K.
Abstract : Cardiovascular disease (CVD) is a leading cause of post–liver transplant death, and variable care patterns may affect outcomes. We aimed to describe epidemiology and outcomes of inpatient CVD care across US hospitals. Using a merged data set from the 2002‐2011 Nationwide Inpatient Sample and the American Hospital Association Annual Survey, we evaluated liver transplant patients admitted primarily with myocardial infarction (MI), stroke (cerebrovascular accident [CVA]), congestive heart failure (CHF), dysrhythmias, cardiac arrest (CA), or malignant hypertension. Patient‐level data include demographics, Charlson comorbidity index, and CVD diagnoses. Facility‐level variables included ownership status, payer‐mix, hospital resources, teaching status, and physician/nursing‐to‐bed ratios. We used generalized estimating equations to evaluate patient‐ and hospital‐level factors associated with mortality. There were 4763 hospitalizations that occurred in 153 facilities (transplant hospitals, n = 80). CVD hospitalizations increased overall by 115% over the decade ( P < 0.01). CVA and MI declined over time (both P < 0.05), but CHF and dysrhythmia grew significantly (both P < 0.03); a total of 19% of hospitalizations were for multiple CVD diagnoses. Transplant hospitals had lower comorbidity patients ( P < 0.001) and greater resource intensity including presence of cardiac intensive care unit, interventional radiology, operating rooms, teaching status, and nursing density (all P < 0.01). Transplant and nontransplant hospitals had similar unadjusted mortality (overall, 3.9%, P = 0.55; by diagnosis, all P > 0.07). Transplant hospitals had significantly longer overall length of stay, higher total costs, and more high‐cost hospitalizations (all P < 0.05). After risk adjustment, transplant hospitals were associated with higher mortality and high‐cost hospitalizations. In conclusion, CVD after liver transplant is evolving and responsible for growing rates of inpatient care. Transplant hospitals are associated with poor outcomes, even after risk adjustment for patient and hospital characteristics, which may be attributable to selective referral of certain patient phenotypes but could also be related to differences in quality of care. Further study is warranted.